1980
DOI: 10.1542/peds.65.3.680b
|View full text |Cite
|
Sign up to set email alerts
|

New Use of a Metal Detector

Abstract: I offer my recent observation on a new technique for following the passage of a coin through the digestive tract. Several months ago I was called by a distraught mother who informed me that her 7-year-old daughter had just swallowed a quarter. X-ray did reveal the coin located in the stomach. I reassured the family informing them that it would pass through in the next few days. After about two weeks of stool gazing and nonpassage the child was x-rayed again, and to my dismay I noted that the coin had not budge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A potential alternative is a hand‐held metal detector (HHMD). This was first described 40 years ago, 13 and studies have reported it to be a sensitive, non‐invasive test 14 . Potential benefits include reduction of radiation burden, improved ED patient flow and cost savings for health‐care systems 15 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…A potential alternative is a hand‐held metal detector (HHMD). This was first described 40 years ago, 13 and studies have reported it to be a sensitive, non‐invasive test 14 . Potential benefits include reduction of radiation burden, improved ED patient flow and cost savings for health‐care systems 15 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%